Discovery and Development of Small Molecule Allosteric Modulators of Glycoprotein Hormone Receptors - Nataraja, Selvaraj G.; Yu, Henry N.; Palmer, Stephen S. (Frontiers in Endocrinology, 2015)
Glycoprotein hormones, follicle-stimulating hormone (FSH), luteinizing hormone (LH), and thyroid stimulating hormone (TSH) are heterodimeric proteins with a common subunit and hormone-specific subunit. These hormones are dominant regulators of reproduction and metabolic processes. Receptors for the glycoprotein hormones belong to the family of G-protein coupled receptors (GPCR). FSH receptor (FSHR) and LH receptor (LHR) are primarily expressed in somatic cells in ovary and testis to promote egg and sperm production in women & men respectively. TSH receptor (TSHR) is expressed in thyroid cells and regulates the secretion of T3 & T4. Glycoprotein hormones bind to the large extracellular domain of the receptor and cause a conformational change in the receptor that leads to activation of more than one intracellular signaling pathway. Several small molecules have been described to activate/inhibit glycoprotein hormone receptors through allosteric sites of the receptor. Small molecule allosteric modulators have the potential to be administered orally to patients thus improving the convenience of treatment. It has been a challenge to develop a small molecule allosteric agonist for glycoprotein hormones that can mimic the agonistic effects of the large natural ligand to activate similar signaling pathways. However, in the past few years, there have been several promising reports describing distinct chemical series with improved potency in preclinical models. In parallel, proposal of new structural model for FSH receptor and in silico docking studies of small molecule ligands to glycoprotein hormone receptors provide a giant leap on the understanding of the mechanism of action of the natural ligands and new chemical entities on the receptors. This review will focus on the current status of small molecule allosteric modulators of glycoprotein hormone receptors, their effects on common signaling pathways in cells, their utility for clinical application as demonstrated in preclinical models, and use of these molecules as novel tools to dissect the molecular signaling pathways of these receptors.